What causes attention deficit hyperactivity disorder?. Issue 3 (7th September 2011) - Thapar, Anita; Cooper, Miriam; Jefferies, Rachel; Stergiakouli, Evangelia
Abstract : Attention deficit hyperactivity disorder (ADHD) affects around 1–3% of children. There is a high level of comorbidity with developmental and learning problems as well as with a variety of psychiatric disorders. ADHD is highly heritable, although there is no single causal risk factor and non-inherited factors also contribute to its aetiology. The genetic and environmental risk factors that have been implicated appear to be associated with a range of neurodevelopmental and neuropsychiatric outcomes, not just ADHD. The evidence to date suggests that both rare and multiple common genetic variants likely contribute to ADHD and modify its phenotype. ADHD or a similar phenotype also appears to be more common in extreme low birth weight and premature children and those exposed to exceptional early adversity. In this review, the authors consider recent developments in the understanding of risk factors that influence ADHD.